Involvement of NADPH Oxidase 1 in Liver Kinase B1-Mediated Effects on Tumor Angiogenesis and Growth - Zulato, Elisabetta; Ciccarese, Francesco; Nardo, Giorgia; Pinazza, Marica; Agnusdei, Valentina; Silic-Benussi, Micol; Ciminale, Vincenzo; Indraccolo, Stefano (Frontiers in Oncology, 2018)
The liver kinase B1 (LKB1) gene is a tumor suppressor with an established role in the control of cell metabolism and oxidative stress. However, whether dis-regulated oxidative stress promotes growth of LKB1-deficient tumors remains substantially unknown. Through in vitro studies, we observed that loss of LKB1 perturbed expression of several genes involved in ROS homeostasis. In particular, this analysis evidenced strongly up-modulated NADPH oxidase 1 (NOX1) transcript levels in tumor cells lacking LKB1. NOX1 accounted in part for enhanced cytotoxic effects of H2O2-induced oxidative stress in A549 LKB1-deficient tumor cells. Notably, genetic and pharmacologic inhibition of NOX1 activity reduced angiogenesis and growth of A549 tumors in mice. These results suggest that NOX1 inhibitors could counteract ROS production and the angiogenic switch in LKB1-deficient tumors.